Porphyrin‐Based Metal–Organic Frameworks for Biomedical Applications - Chen, Jiajie (Angew Chem Int Ed Engl, 2020)
Porphyrins and porphyrin derivatives have been widely explored for various applications owing to their excellent photophysical and electrochemical properties. However, inherent shortcomings, such as instability and self‐quenching under physiological conditions, limit their biomedical applications. In recent years, metal–organic frameworks (MOFs) have received increasing attention. The construction of porphyrin‐based MOFs by introducing porphyrin molecules into MOFs or using porphyrins as organic linkers to form MOFs can combine the unique features of porphyrins and MOFs as well as overcome the limitations of porphyrins. This Review summarizes important synthesis strategies for porphyrin‐based MOFs including porphyrin@MOFs, porphyrinic MOFs, and composite porphyrinic MOFs, and highlights recent achievements and progress in the development of porphyrin‐based MOFs for biomedical applications in tumor therapy and biosensing. Finally, the challenges and prospects presented by this class of emerging materials for biomedical applications are discussed.